Retention of nickel, cobalt and chromium in skin at conditions mimicking intense hand hygiene practices using water, soap, and hand-disinfectant in vitro - Vilela, Libe; Schenk, Linda; Julander, Anneli; Midander, Klara (Journal of occupational medicine and toxicology (London, England), 2024)
Background During the COVID-19 pandemic, increased hand hygiene practices using water, soap and hand disinfectants, became prevalent, particularly among frontline workers. This study investigates the impact of these practices on the skin’s ability to retain the allergenic metals nickel, cobalt, and chromium. The study constitutes three parts: (I) creating an impaired skin barrier, (II) exposing treated and untreated skin to nickel alone, and (III) in co-exposure with cobalt and chromium. Methods Using full-thickness skin from stillborn piglets, in vitro experiments were conducted to assess retention of metals in skin at conditions mimicking intense hand hygiene practices. Treatment of skin with varying concentrations of sodium lauryl sulphate (SLS), to impair its barrier integrity was assessed. This was followed by exposure of treated and untreated skin to the metals, that were dissolved in Milli-Q water, 0.5% SLS, and ethanol respectively. Results Results showed that pre-treatment with 5% SLS impaired the skin barrier with regards to the measure of trans epidermal water loss (TEWL). Metal amounts retained in the skin were generally higher in treated than untreated skin. The highest amounts of metal retained in skin were observed for exposure to nickel in ethanol. Co-exposure to nickel, cobalt, and chromium in 0.5% SLS resulted in the highest amounts of total metal retention. Conclusions The in vitro findings highlight the increased risk of metal retention in skin due to an impaired barrier. The SLS concentration used in the current study corresponds to those used in many hand hygiene products. Hence, occupational settings with frequent exposure to water, soap and disinfectants need to consider protective measures not only for the irritant exposures themselves but also simultaneous exposure to allergenic metals.